KEWENANGAN PROFESI DAN KEAMANAN (PROPAM)DALAM PENEGAKAN HUKUM DAN KODE ETIK KEPOLISIAN REPUBLIK INDONESIA (STUDI KASUS PENINDAKAN PROPAM TERHADAP OKNUM KEPOLISIAN PELAKU PEMERKOSAAN) - Oktavian Brian Firmansyah; Siti Marwiyah; Sri Astutik; Subekti (Judge : Jurnal Hukum, 2025)
Abstract This study examines the authority of the Indonesian National Police’s Division of Profession and Security (PROPAM) in enforcing law and the professional code of ethics, focusing on a case involving disciplinary action against a police officer who committed rape. Using a normative juridical approach, the research collects data through literature review, documentation, and analysis of relevant regulations such as Police Regulation No. 7 of 2022 and Law No. 2 of 2002. Findings indicate that PROPAM plays a strategic role in maintaining the integrity of the police institution, with powers including conducting internal investigations, seizing evidence, and recommending administrative sanctions up to dishonorable discharge. However, weaknesses remain in transparency, structural independence, and openness to external oversight. While PROPAM’s handling of the rape case demonstrates serious ethical enforcement, systemic reforms are necessary to strengthen accountability and professionalism within the police force